International Workshop “The Varieties of Power in the Economy,” Laboratory for Studies in Economic Sociology, NRU HSE, Moscow, Russia, July 2–3, 2020 - Lebedeva, Daria (Journal of Economic Sociology, 2020)
The international workshop ‘The Varieties of Power in the Economy’ was held from July 3 to 4, 2020 in Moscow, Russia. The seminar was organized by the Laboratory for Studies in Economic Sociology (LSES) at the National Research University Higher School of Economics, Moscow. The seminar primarily aimed to initiate a discussion on power practices, modes of influence, compliance, and governance structures in the economy. The keynote speakers of the workshop were Alena Ledeneva, Professor of Politics and Society at the School of Slavonic and East European Studies (University College London, UK) and Valery Yackubovich, Professor at the Management Department (SSEC Business School, France). In their lectures they shared their understanding of the topics and how they can be incorporated in various conceptual frameworks within economic sociology. Apart from LSES, the seminar engaged researchers from various research institutions, backgrounds, and traditions. Invited speakers included Elena Bogdanova (University of Gothenburg), Tamara Kusimova (Central European University), Aleksei Pobedonostsev (The European University Institute in Florence), Olga Sidenko (Voronezh State University), Daria Shcheglova (HSE University—Institute of Education), Maria Tysiachniouk (University of Wisconsin-Madison), Ulla Paper, Stanislav Klimovich, and Katharina Bluhm (Freie Universität Berlin), and Maya Shmidt (Uppsala University). The researchers took a closer look at their academic fields and identified the issues of power practices, forms of influence, and control in economic exchange. By examining completely different social spheres and institutional fields, the participants discussed the ambivalence of power and the variety of power relations and practices in the economy.